Myocardial revascularization - Larre Borges, U; Altieri, C; Bonilla, C; Lanza, M (Cirugía del Uruguay, 2020)
The paper presents sone experimental work on the study of miocardial revascularization as per Vineberg's technique, and the results thereof are analyzed.